Synthesis and characterizations of phthaloyl chitosan-based polymer electrolytes - Aziz, N.A.; Majid, Siti Rohana; Arof, Abdul Kariem (Elsevier, 2012)
Phthaloyl chitosan (PhCh) has been synthesized by reacting excess phthalic anhydride with chitosan in the presence of nitrogen gas (N-2). Confirmation of phthaloyl chitosan structure by Fourier-transform infrared (FTIR) spectroscopy shows bands at 1773 and 1713 cm(-1) attributable to the pthalimido group. From X-ray diffraction (XRD), the samples are largely amorphous. Thermal stability of chitosan is increased on phthaloylation. Ammonium thiocyanate (NH4SCN) salt has been added to the solution of phthaloyl chitosan in N,N-dimethylformamide (DMF) before casting to form films. The amount of NH4SCN salt added ranges from 5 to 50 wt. % concentration. The highest conductivity at 298 K is (2.42 +/- 0.01) x 10(-5) S cm(-1) for the sample 70 wt. % PhCh-30 wt. % NH4SCN. Impedance of the films has been measured at temperatures between 298 K and 373 K and in the frequency range from 0.1 Hz to 1 x 10(7) Hz. Relaxation peaks are observed from dielectric loss and tangent delta variation with frequency at ambient and elevated temperatures in the frequency range investigated for the highest conducting sample. Decomposition voltage is similar to 2.07 V and transference number measurements show that charge conduction is mainly by ions. (C) 2012 Elsevier B.V. All rights reserved.